1995
DOI: 10.2307/5802
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Strategy of the Herring Gull: Changes in Survival and Fecundity in a Population Subjected to Various Feeding Conditions

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. The present study compares breeding par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 34 publications
7
81
0
6
Order By: Relevance
“…A similar positive relationship between food abundance in rubbish dumps and clutch size was found by Pons & Migot (1995) in Herring Gulls. Reduction in food supply, resulting from the closure of a rubbish dump, was followed by a decrease of 6.7% in mean clutch sizes and a 50% reduction in production of young.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A similar positive relationship between food abundance in rubbish dumps and clutch size was found by Pons & Migot (1995) in Herring Gulls. Reduction in food supply, resulting from the closure of a rubbish dump, was followed by a decrease of 6.7% in mean clutch sizes and a 50% reduction in production of young.…”
Section: Discussionsupporting
confidence: 58%
“…The food provided by garbage seems to affect migrating habits of White Storks (Tortosa et al 1995). Breeding performance is also known to be affected by food availability at dumps as reported in the White Stork (Tortosa et al 2002) and Herring Gulls Larus argentatus (Pons & Migot 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that there is a relationship between resource availability and deferred breeding (e.g. Monaghan et al 1992;Wernham & Bryant 1998), adult survival (Pons & Migot 1995;Harris et al 1997;Oro et al 1999;Oro & Furness 2002) or local recruitment rates (Boekelheide & Ainley 1989;Oro & Pradel 2000). Most survival studies have been conducted at a single site, or a subset of locations and have addressed local survival (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The main prehatch factor affecting egg size is food availability (see e.g. Hébert and Barclay, 1988;Hiom et al, 1991;Bolton et al, 1992;Pons and Migot, 1995), so egg size reflects the conditions of food availability in the area surrounding colonies SCI. MAR., SCIENTIA MARINA…”
Section: Introductionmentioning
confidence: 99%